Si-FITÓLITOS EM EUDICOTILEDÔNEAS E SEU POTENCIAL NA DESCONTAMINAÇÃO DE SOLOS CONTENDO METAIS PESADOS: Si-Phytoliths in Eudicots and their potential on decontamination of soils containing heavy metals. - Fernandes Horn, Heloiza Márcia; Horn, Adolf Heinrich; Sampaio, Regynaldo Arruda; Rodrigues, Márcio Neves; Alvarenga, Anarelly Costa; Lepsch, Igo Fernando (Geochimica Brasiliensis, 2020)
For the decontamination of soils, rich in heavy metals are proposed various methods and procedures. Among them, one is the phytoremediation. The present study investigates the phytoremediation by phytoliths. In this text three native plants from the Cerrado biome with ability to produce Si-phytoliths, were investigated. The studied plants are Rollinia leptopetala, Piptadenia gonoacantha and Sida sp. The results showed that the studied species concentrated heavy metals in Si-phytoliths in different concentrations in their organs (leaves, stems, roots). The concentration in plants increases with the highest available concentration in the soil. Si-phytoliths extracted from the soil (with small amounts of other compounds such as oxides, clays <1-3%) show concentrations comparable to average concentrations of the studied plants. Thus, the available metals are transformed into non-available ones, which allows the use of these plants for decontamination.